Exploring Social Remittances and Transnational Activism Amongst Transgender Refugees - Soloaga, Isabel (Frontiers in Human Dynamics, 2021)
This paper explores how transgender refugees living in the United Kingdom, Europe and the United States leverage social remittances and transnational ties to advocate for their rights within intolerant receiving countries. Even after migration, their frequent experiences of persecution in so-called “safe” countries often necessitate a continuation of their activism. This study centers on the lived experiences of transgender refugees through a combination of case studies, interviews, and participatory photography. Focusing on three case studies, it analyzes the role of social remittances and transnational ties in the activism of transgender refugees. The results illustrate how transgender individuals build activist networks through interpersonal connections, especially within what research participants described as “chosen families” in receiving countries. Grassroots nonprofit organizations serving transgender refugees prove essential to building this collectivity formation. Such organizations act as loci of activism and allow for safe sharing of lifesaving social remittances to those still living in origin countries. In addition, new technologies, including end-to-end encrypted messaging platforms, allow for the secure one-on-one exchange of ideas and survival practices around gender identity. This sharing creates a ripple effect, leading to the creation of robust transnational networks between transgender activists worldwide. I argue that systemic oppression, racism, and transphobia in receiving countries push transgender refugees, victims of violence worldwide, into roles as activists. By investing in chosen families, participating in nonprofit organizations dedicated to supporting transgender refugees, and sharing their activism worldwide through transnational networks, transgender refugee activists fight to access their fundamental human rights.